Assessment of procurement function and corporate planning strategy of public limited liability companies in the sekondi-takoradi metropolis of ghana - QUANSAH JOSEPH (KNUST, 2024)
A thesis submitted to the department of supply chain and information systems, Kwame Nkrumah university of science and technology, Kumasi in partial fulfillment of the requirements for the award of the degree of master of science in logistics and supply chain management